Modelo de maturidade em gerenciamento de portf??lio de projetos para a Administra????o Direta Federal - Almeida, Ta??sa Aparecida Ribas de (2016)
The main objective of this research is to propose a project portfolio management maturity model adapted to the Brazilian Federal Direct Public Administration. For this, a literature review on issues related to that goal was developed, from which relevant publications to the theoretical foundation of the proposed research model have been identified. Based on the literature review and using the content analysis method, which consists of systematic procedures that provide quantitative or qualitative indicators, it was possible to develop a maturity model of project portfolio management aligned to the Portfolio Management methodology of the Information Technology Resources System (MGPP-SISP) under the Ministry of Planning, Budget and Management. The model was evaluated to a focal group of experts to collect the perspectives and experiences of the participants. The present study proposes a project portfolio management maturity model adapted to MGPP-SISP for organizations of the Brazilian Federal Direct Public Administration.